Micro irrigation engineering for horticultural crops : policy options, scheduling, and design - Goyal, Megh Raj; Singh, Ajai, 1970- (Waretown, NJ : Apple Academic Press, 2017)
"This book presents a variety of policy adoption methods, irrigation scheduling, and design procedures in micro irrigation engineering for horticultural crops. The chapters range from policy interventions to applications of systems for different crops and under different land conditions. Compiling valuable information and research, the book is divided into three main sections: Policy Options: Drip Irrigation Among Adopters Irrigation Scheduling of Horticultural Crops Design of Drip Irrigation Systems. The editors present valuable research and information on micro irrigation methods in an effort to focus on innovation and evolving new paradigms for efficient utilization of water resources. The adoption of micro irrigation systems can be a panacea for irrigation related problems and can help to increase the yield and area under cultivation, especially for small farmers without abundant technological resources. Micro Irrigation Engineering for Horticultural Crops: Policy Options, Scheduling, and Design will be valuable for agricultural engineering students, irrigation engineers, and scientists/professors in engineering."--Provided by publisher.
Opinion of adopters and nonadopters toward drip irrigation: insights for marketing / Vaibhav Bhamoriya -- Policy options for better implementation of micro irrigation: case study of India / K. Palanisami, K. Krishna Reddy, S. Raman, and T. Mohanasundari -- Drip and surface irrigation methods: irrigation scheduling of onion, cauliflower, and tomato / S.K. Srivastava -- Tensiometer-based irrigation scheduling: drip-irrigated bell pepper under naturally ventilated polyhouse / Ashwani Kumar Madile and P.K. Singh -- Open and covered cultivation: irrigation and fertigation scheduling / P.K. Singh -- Drip irrigation and fertigation for horticultural crops: scope, principle, basic components, and methods / Murtuza Hasan -- Design of micro irrigation system: sloppy and terraced land / P.K. Singh, K.K. Singh, R. Singh, and H.S. Chauhan -- Uniformity measurement methods: spinner-type micro-sprinklers / V. Manjunatha, Surjeet Singh, and Ajai Singh.
Keywords: Microirrigation